The Influence of Work Spirit, Leadership Style and Work Ethic on Employee Achievement of Universitas Pembangunan Panca Budi Medan - Damayanti, Riski; Farida Ferine, Kiki (CV. Lafadz Jaya, 2023)
The purpose of this research is to find out whether work enthusiasm simultaneously and partially has a positive and significant effect on the work performance of Universitas Pembangunan Panca Budi employees, to find out whether leadership style simultaneously and partially has a positive and significant effect on the work performance of Universitas Pembangunan Panca Budi employees, to find out whether work ethic simultaneously and partially has a positive and significant effect on the work performance of Universitas Pembangunan Panca Budi employees. This research was carried out from December 2022 to July 2023, this research used quantitative methods. The population of this study was all employees of Universitas Pembangunan Panca Budi, totaling 198 people, the sample size in this study was 132 employees of Universitas Pembangunan Panca Budi, this sampling used the Slovin formula, in this study the data used was premier data, namely data obtained from questionnaires. Data processing in this research uses the SPSS software program. From the data obtained, the overall coefficient value exceeds 0.30, it can be stated that all question items and scores obtained are valid.